(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
It must take into account the development that has occurred in business organizations environment which required internal audit function to evolve to be include the aspects of operational audit and to provide administrative and technical consulting is done by increasing the audit scope to include the external environment study , in addition to internal environment, and can be achieved through the adoption of the strategic audit And use its tools The research problem is that the traditional internal audit programs compatible with environment internal and external of organizations, the research aims to identify the concept of strategic audit of business organizations as well as the design of a proposed work program to develop the internal audit includes strategic audit procedures. The research has come to a set of conclusions and recommendations, the most important conclusions represent: the research revealed that it can develop internal audit services through the adoption of the audit program includes steps and procedures for strategic audit by internal auditors, and that apparently appear through descriptive analysis of the research variables, and the internal audit does not adds value to the company without taking into consideration the study objectives and strategies when planning and implementation of the process of internal audit. The most important recommendations are: the need to use strategic audit tools by internal auditors and work to expand the scope of internal audit work to include the external environment of the facility in addition to its internal environment and the adoption of the proposed internal audit program, the internal auditor must audit the objectives of the company’s strategic and verify the compatibility with the vision and mission of the company as well as with its detailed plan , as well as the need to involve internal auditors training courses and qualification in the field of strategic auditing methods such as SWOT analysis tool, todevelop their scientific and practical skills